2017
DOI: 10.3126/jnarc.v3i1.17275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sucrose and Growth Regulator’s Level on Ginger Micropropagation

Abstract: Ginger is most important cash crop of the hilly region of Nepal. However, availability of disease free planting material (rhizome) is the major problem faced by Nepalese farmers. Tissue culture is the only option to produce disease free rhizome of ginger. Suitable culture media combination is most important for the production of planting material in ginger through tissue culture. Therefore, effect of different level of sucrose and growth regulators on micro-propagation of ginger was studied using local collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The number of ginger plantlets and in vitro roots decreased at a concentration of 60 g.l -1 sucrose in other investigations as well [2,24]. Though, 60 g.l -1 was informed as the most suitable concentration for micro rhizome production in Z. officinale [4,24].…”
Section: Effect Of Plant Growth Regulators On the Shoot And Root Numb...mentioning
confidence: 66%
See 1 more Smart Citation
“…The number of ginger plantlets and in vitro roots decreased at a concentration of 60 g.l -1 sucrose in other investigations as well [2,24]. Though, 60 g.l -1 was informed as the most suitable concentration for micro rhizome production in Z. officinale [4,24].…”
Section: Effect Of Plant Growth Regulators On the Shoot And Root Numb...mentioning
confidence: 66%
“…A previous study informed that red ginger explants produced more plantlets and roots at a concentration of 30 g.l -1 sucrose than at 10 and 15 g.l -1 , but 45 g.l -1 was the optimum concentration because the treated explants multiplied the number of plantlets and roots per explant while decreasing the average length of the roots [2]. The number of ginger plantlets and in vitro roots decreased at a concentration of 60 g.l -1 sucrose in other investigations as well [2,24]. Though, 60 g.l -1 was informed as the most suitable concentration for micro rhizome production in Z. officinale [4,24].…”
Section: Effect Of Plant Growth Regulators On the Shoot And Root Numb...mentioning
confidence: 77%
“…Inden et al, 1988 [29] reported that high concentrations of growth regulators can reduce shoot elongation, reduced rooting and caused genetic instability in ginger. Amgai et al, 2017 [30] reported the influence of sucrose in the rhizome weight and the also the addition of NAA in ginger micropropagation. i.e; MS basal media with 60 g/L sucrose+5 mg/L BA+0.5 mg/L NAA had more rhizome weight compared to other lower levels of sucrose.…”
Section: Utilization Of Plant Growth Regulators In Tissue Culture Of ...mentioning
confidence: 99%
“…Clonal propagation of ginger is a well-established technology throughout the world. Shoot tips, axillary buds, root tips, rhizome axillary buds, vegetative buds, sprouting buds, young buds, and rhizome buds have been used as explants for in vitro regeneration of many ginger varieties successfully [3,5,6,13,[18][19][20][21]. Likewise, clonal propagation of many Ethiopian ginger cultivars was attempted successfully using rhizome buds, shoot tips, and others sources of explants [10,13].…”
Section: Introductionmentioning
confidence: 99%